DNA Polymorphism of D1S80 Locus in Modern Malay Sample Population of Sarawak (DNA Polimorfisma di Lokus DIS80 dalam Sampel Populasi Melayu Moden Sarawak) - Hairul, Azman Roslan; Nur Hafizah, Azizan (Researchgate, 2009)
The molecular genetic marker, minisatellite locus D1S80 (1p35-p36), is a highly polymorphic variable number of tandem repeats (VNTR). Its polymorphic nature allows for phylogenetic studies, forensic analysis, genetic maps construction and paternity testing to be performed. A study of the hypervariable locus D1S80 was conducted to determine the allele frequency and distribution of this locus in modern Malay in Sarawak population. The polymerase chain reaction technique was employed and results were analysed on polyacrylamide gel. A total of seventy-six DNA samples of unrelated Malay individuals in UNIMAS were collected and examined. The VNTR analysis of the D1S80 locus demonstrated the presence of 17 alleles in the Malay population. Allele with the size of 577 bp (27 repeats) was determined to be the most common in the sample population with the frequency of 0.1641, followed by allele with the size of 561 bp (26 repeats) and 529 bp (24 repeats) whose frequency is 0.1172 and 0.1094, respectively. The smallest allele is allele with the size of 465 bp (20 repeats) whereas the largest is allele with the size of 753 bp (38 repeats). The sample population exhibited 57.8% heterozygosity.